Impact of Creativity on Students’ Entrepreneurial Intention: Study Case on Jakarta - Anggraeny, Chuurur Roshi (APPS Publications, 2023)
This study examines the factors that affect individuals’ entrepreneurial intention, especially among university students. The study employed a quantitative approach and applied descriptive analysis as a methodological approach to investigate the students’ entrepreneurial intention using Smart-PLS software to test the hypotheses. The results showed that entrepreneurial intention is positively and significantly influenced by attitude toward self-employment. Besides, this study confirmed significant effect of creativity on attitude toward self-employment, which later affect entrepreneurial intention. This study contributes to adding to the literature on the factors determining entrepreneurial intention and provides empirical support for university that encourage university students to practice entrepreneurship.